The effects of elevated hearing thresholds on performance in a paintball simulation of individual dismounted combat. (23rd January 2017) - Sheffield, Benjamin; Brungart, Douglas; Tufts, Jennifer; Ness, James
Abstract: Objective : To examine the relationship between hearing acuity and operational performance in simulated dismounted combat. Design : Individuals wearing hearing loss simulation systems competed in a paintball-based exercise where the objective was to be the last player remaining. Four hearing loss profiles were tested in each round (no hearing loss, mild, moderate and severe) and four rounds were played to make up a match. This allowed counterbalancing of simulated hearing loss across participants. Study sample : Forty-three participants across two data collection sites (Fort Detrick, Maryland and the United States Military Academy, New York). All participants self-reported normal hearing except for two who reported mild hearing loss. Results : Impaired hearing had a greater impact on the offensive capabilities of participants than it did on their "survival", likely due to the tendency for individuals with simulated impairment to adopt a more conservative behavioural strategy than those with normal hearing. Conclusions : These preliminary results provide valuable insights into the impact of impaired hearing on combat effectiveness, with implications for the development of improved auditory fitness-for-duty standards, the establishment of performance requirements for hearing protection technologies, and the refinement of strategies to train military personnel on how to use hearing protection in combat environments.